Pendampingan Masjid Baitus Shomad Desa Tegalombo Kabupaten Pacitan sebagai Pusat Pengembangan UMKM Masyarakat Berbasis Nilai-Nilai Islam - Ismail, Ismail (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Mosques have strategic potential not only as places of worship but also as centers for social and economic empowerment of the community. However, this potential has not been optimally utilized, particularly in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in rural areas. This community service program aims to assist Baitus Shomad Mosque in Tegalombo Village, Pacitan Regency, to function as a center for MSME development based on Islamic values. The study employed a qualitative approach using the Participatory Action Research (PAR) model, involving mosque administrators, MSME actors, and community leaders actively in all stages of the program. Data were collected through participatory observation, in-depth interviews, focus group discussions, and documentation. The results indicate a strengthening of the mosque’s role as a hub for socio-economic activities, an increase in MSME capacity in business management, and the internalization of Islamic values such as honesty, trustworthiness, and justice in business practices. Furthermore, the mentoring activities fostered the formation of community-based business networks and enhanced social solidarity among community members. This program concludes that mosque-based assistance can encourage gradual and sustainable social and economic transformation and has the potential to serve as a contextual and applicable model for rural community empowerment.